Comparison of combined low-dose hormone therapy vs. tibolone in the prevention of bone loss. (2nd September 2016) - Kalder, M.; Kyvernitakis, I.; Hars, O.; Kauka, A.; Hadji, P.
Abstract: Objectives: To compare the effects on bone mineral density (BMD) measured by dual-energy X-ray absorptiometry at the lumbar spine, the femoral neck and the total hip following 2 years of treatment with a low-dose combined hormone therapy (HT) comprised of 1 mg estradiol and 0.5 mg norethisterone acetate (E2/NETA) versus 2.5 mg tibolone in postmenopausal women. Additionally, quantitative ultrasonometry (QUS) of the os calcaneus and of the phalanges was performed. Methods: Changes in BMD, QUS and side-effects were assessed at baseline, 6, 12 and 24 months in 50 postmenopausal women who received either E2/NETA ( n = 26) or tibolone ( n = 24) for 2 years. Results: Compared to women on tibolone, women receiving E2/NETA showed a significant increase in BMD from baseline to 12 and 24 months at the lumbar spine (3.07%, 3.86%; p < 0.01 vs. 1.13%, 2.23%; p < 0.05), and at the total hip (1.33%, 1.69%; p < 0.01 vs. 0.76%, 0.70%) and at the femoral neck from baseline to 24 months (1.10%; p < 0.05). QUS indices only showed a significant change with the ultrasound bone profile index with E2/NETA at 6 months (-2.32%; p < 0.001). Conclusions: Low-dose E2/NETA showed a significantly higher increase in BMD compared to tibolone. QUS measurement was not considered to comprise beneficial effects in monitoring drug-induced bone changes.